Business cycles in the motor insurance in Poland - Poprawska, Ewa; Jędrzychowska, Anna (Cykle koniunkturalne na polskim rynku ubezpieczeń komunikacyjnych, 2011)
The aim of this paper is to analyze the changes in the motor insurance market in Poland through the analysis of business cycles that have occurred in this area and the comparison of changes in EU countries. Such studies give an opportunity to explore the current insurance market trends and predict future behavior and have also practical significance as they provide the possibility of preparing for cyclical changes. In Poland, the indicator of cyclical fluctuations in the insurance area is the synthetic indicator PIKU (Poznański Indeks Koniunktury Ubezpieczeniowej, in English: Poznań Insurance Business Index). Other measures which are worth examining are claims ratio and combined ratio – they will be also analyzed and compared with similar ratios in EU countries
Ekonomia = Economics, 2011, Nr 2 (14), s. 281-290
Keywords: motor insurance; business cycles; PIKU; claims ratio